Analytical study of the influence of church institutionalism using an intergenerational approach and Jürgen Habermas’s communication theory - Zacharias, Triardi Samuel (Institut Agama Kristen Negeri Toraja, 2025)
This article explores how institutionalism in the church creates a generation gap, consolidates power, and suppresses the creativity and active participation of church members. Church institutionalism is understood as a framework that influences every church practice not limited to the notion of church as an institution or organization. Whether we realize it or not, the church model that is increasingly reinforced by institutional patterns has a significant impact on the participatory inequality of each church member. when the discourse or let’s say the line of church authority is dominated by one party for example by the elders or even by the youth, then what happens is discrimination and the strengthening of exclusivism in the communion together. therefore, an intergenerational approach is proposed to bridge institutionalism and communalism, emphasizing the importance of equal, participatory, and critical communication. This article emphasizes that by critically reflecting on the intergenerational approach and Jürgen Habermas’s theory of communication, churches can strengthen intergenerational relations and create a more inclusive and emancipatory environment. By examining the phenomenon of church institutionalism, intergenerational theory and Habermas’s communication theory, the discourse between these perspectives can be further explored. This discussion is expected to generate momentum for the creation of a more equitable and participatory communication model that bridges the emerging generational gap within the church community.